(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This paper examines the didactic possibilities of integrating General Pedagogy with the Methodology of Teaching Physics and Astronomy in the preparation of future teachers. The study is based on a design-oriented analysis of the dissertation plan for the 60110700 - Physics and Astronomy educational direction, where methodological competence is interpreted as a system of cognitive-integrative, lesson-design, practical-methodological, digitalmethodological, communicative, and diagnostic-reflective components. The research aim is to clarify how general pedagogical concepts such as learning objectives, teaching methods, assessment, STEAM education, problem-based learning, case study, project work, and reflection can be connected with physics and astronomy teaching tasks. The methodology relies on document analysis, competence mapping, and construction of an integration chain: pedagogical concept - physics or astronomy topic - methodological problem - digital tool - assessment - reflection. The results present an integration matrix and a set of competence-oriented tasks, including lesson plans, methodological cases, virtual laboratory analysis, PISA-type assignments, STEAM projects, and reflective portfolios. The discussion shows that such integration can make teacher preparation more coherent, practice-oriented, and measurable. The article concludes that systematic integration of pedagogical theory and subject methodology is a necessary didactic condition for developing future physics and astronomy teachers’ methodological competence.